The Impact of Political Change on the State of Academia Including Academic Freedom in the Arab World: Libya as a Case Study. Issue 2 (2nd April 2020) - Derbesh, Mabruk
ABSTRACT: Furthering Western style academic freedom has been challenging, as Arab countries, especially Libya, have known only autocratic regimes throughout their modern existence. Amidst its current political and social upheaval, Libyan society is drifting towards the unknown. The problem addressed in this study is the impact of political change on the state of academia but, more specifically, academic freedom. Since the intervention in Libya by NATO states, many academics have lost their jobs. Some have become refugees outside of Libya as a direct result of the appropriation of most of the governmental posts in the country by religious and political radicals. The research questions reflect ways in which the new inserted de facto leaders of post-transitional Libya have impacted life on Libyan campuses and academic freedom.